El control de los organismos reguladores: del régimen de barreras burocráticas a la revisión judicial - Gamarra Abarca, Sebastian (Pontificia Universidad Católica del Perú, 2025)
Within the framework of administrative claims, the article analyzes the interactions between the resolution bodies of Indecopi (Commission for the Elimination of Bureaucratic Barriers and the Specialized Chamber for the Elimination of Bureaucratic Barriers) and the regulatory agencies, in order to identify the main limitations of the administrative jurisdiction, which come, among others, from the provisions of Legislative Decree 1256 and the jurisprudence of Indecopi. This situation generates control gaps that, in turn, result in the lack of protection of the citizens. To better illustrate this scenario, a historical overview of the Peruvian institutions involved is carried out, leading to a detailed review of the applicable regulations and jurisprudence. Finally, it concludes with the proposal of possible alternatives for improvement, emphasizing the revitalization of the Judicial Branch possible alternatives for improvement.

En el marco de las denuncias administrativas, el artículo analiza las interacciones entre los órganos resolutivos del Indecopi (Comisión de Eliminación de Barreras Burocráticas y Sala Especializada en Eliminación de Barreras Burocráticas) y los organismos reguladores, a fin de identificar las principales limitaciones de la jurisdicción administrativa, las cuales se derivan, entre otras, de las disposiciones del Decreto Legislativo 1256 y la jurisprudencia del Indecopi. Dicha situación genera vacíos de control que, a su vez, resultan en la desprotección para los administrados. Para ilustrar mejor este escenario, se realiza un recorrido histórico de las instituciones peruanas implicadas, hasta llegar a una revisión detallada de la normativa y jurisprudencia aplicable. Finalmente, se concluye con la propuesta de posibles alternativas de mejora, haciendo énfasis en la revitalización del Poder Judicial.
Oversighting the regulatory agencies: from the regime of bureaucratic barriers to judicial review
Keywords: Administrative claims; Resolution bodies of Indecopi; Elimination of bureaucratic barriers; Limitations of administrative jurisdiction; Judiciary; Denuncias administrativas; Órganos resolutivos del Indecopi; Eliminación de barreras burocráticas; Limitaciones de la jurisdicción administrativa; Poder Judicial; https://purl.org/pe-repo/ocde/ford#5.05.01